Female’s Participation through First-Past-the-Post Electoral System in Provincial Election of Nepal - Khadka, Gopal (Patan Pragya, 2023)
An election produces changes in the socio-cultural arena. The gender gap is commonly used in politics to indicate voting preferences and level of participation during pre-electoral, electoral and post-electoral activities. Gender gap creates obstacles in every step of gender mainstreaming. This article was prepared based on secondary data from the election commission, Nepal (ECN). To assess the status of female’s participation and to identify causes and measures of the gender gap in the provincial level first-past-the-post electoral system, this article was prepared as the title female’s participation through first-past-the-post electoral system in the provincial election of Nepal. A simple literature review was conducted to collect essential information to meet the objective. The status of female’s participation is found low at the provincial level first-past-the-post electoral system in Nepal. There were few numbers of nominate female candidates and elected female candidates in all 7 provinces. In Karnali province, even a single female candidate can’t win the race. To meet the national commitment in gender mainstreaming and to fulfill the target of sustainable development goals, all political parties must perform effective policy to increase the number of female candidates. Through politics, women can realize discrimination and destitution over them. Active participation of women in politics boosts up their roles as voters, candidates, elected officials, electoral administrators, observers, civil society representatives, etc. All barriers regarding female participation in politics must be corrected by concerned authorities as soon as possible with the visionary and coordinating leadership of the local, provincial, and federal government.